2014
DOI: 10.1155/2014/707310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1.5% Dish Washing Solution and 95% Lemon Water in Substituting Perilous Xylene as a Deparaffinizing Agent for Routine H and E Staining Procedure: A Short Study

Abstract: Aim. To assess the efficacy of dish washing solution and diluted lemon water in deparaffinizing sections during conventional hematoxylin and eosin staining technique. Objective. The objective is to utilize eco-friendly economical substitute for xylene. Materials and Methods. Using twenty paraffin embedded tissue blocks, three sections each were prepared. One section was stained with conventional H and E method (Group A) and the other two sections with xylene-free (XF) H and E (Groups B and C). Staining charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…[ 2 ] Lemon water is used to brighten the copper utensils, to remove grease and polish, and as sanitary kitchen deodorizer. [ 9 ] Coconut oil is an easily available colorless solution generally used in lotions and ointments, as hair oil, in laxatives, and for cooking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Lemon water is used to brighten the copper utensils, to remove grease and polish, and as sanitary kitchen deodorizer. [ 9 ] Coconut oil is an easily available colorless solution generally used in lotions and ointments, as hair oil, in laxatives, and for cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Premalatha et al . [ 5 ] also used mineral oil as a deparaffinizing agent and Ananthaneni et al [ 9 ] attempted to use lemon water as a dewaxing agent.…”
Section: Introductionmentioning
confidence: 99%
“…used 1.5% DWS and 95% DLW as deparaffinizing agents in routine H and E staining and found that 1.5% DWS revealed comparatively superior uniform staining and less retention of wax compared to 95% DLW. [ 17 ] Sermadi et al . used coconut oil as an alternative in tissue processing and found it as an efficient substitute for xylene causing less shrinkage of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Clearing is an important step in the production of histological sections with the aim of removing alcohol and other dehydrating fluids from tissue prior to infiltration of the embedding material, which is usually paraffin wax. Over the years, xylene which is naturally available in coal tar and petroleum has been widely used as a clearing agent chiefly because of its excellent compatibility with alcohol and paraffin wax, where it causes maximum displacement of alcohol and makes the tissue transparent thus enhancing paraffin infiltration coupled with its use as a deparaffinizing agent in staining and application of coverslip to stained slides [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%